TRANSFORMASI HUKUM KELUARGA DI TUNISIA: STUDI ATAS REFORMASI LEGISLASI DAN TANTANGAN SOSIO-RELIGIUS DALAM PERSPEKTIF MAQASHID AL-SHARIAH - Nasharuddin, Rifan; Syarifuddin, Syarifuddin; Murtadho, Ali (Jurnal AL-SYAKHSHIYYAH Jurnal Hukum Keluarga Islam dan Kemanusiaan, 2025)
Tunisia stands out as one of the most progressive Muslim-majority countries in reforming family law in the post-independence era. This reform was marked by the promulgation of the Code du Statut Personnel (CSP) in 1956, which abolished polygamy, restructured divorce rights, and enhanced protections for women and children. This study aims to analyze the dynamics of family law reform in Tunisia using a normative-juridical and historical-comparative approach, while also examining how contextual ijtihad has been employed to transform Islamic law within a modern state framework. The findings reveal that Tunisia’s success in legal reform was driven by strong political will, active civil society engagement, and the use of maqashid al-shariah (objectives of Islamic law) as a foundation to achieve substantive justice. However, the reform efforts also faced challenges, including cultural resistance and political shifts following the Arab Spring. This study asserts that Islamic family law can be reinterpreted progressively through maqashid-based approaches and human rights principles without losing its Islamic identity. Tunisia thus provides an important precedent for other Muslim-majority countries seeking to establish a just, equitable, and contextually responsive family law system.